The Impact of the Ketogenic Diet on Athletic Performance: A Systematic Literature Review - Bartosik, Kacper; Furtek, Dawid; Ostrowicz, Klaudia; Kurenda, Kinga (Quality in Sport, 2025)
Introduction The low-carbohydrate, high-fat ketogenic diet (K-LCHF) is gaining popularity among athletes as a potential strategy for improving body composition and physical performance. It is based on restricting carbohydrate intake to a level that induces ketosis while increasing dietary fat consumption. This study aimed to review the current literature on the effects of the K-LCHF diet on athletic performance and to identify possible adverse effects associated with its use. Current State of Knowledge Scientific articles published between 2020 and 2025 were analyzed using PubMed, Scopus, and Google Scholar databases. Both original studies and reviews focusing on athletes and physically active individuals were included. Findings suggest that while the K-LCHF diet may promote weight loss, it does not consistently improve aerobic capacity, strength, or speed. In some athletes, performance decline, disturbances in calcium-phosphate metabolism, changes in iron metabolism, and inflammatory markers were observed. Benefits appear more pronounced in individuals who are overweight or participating in non-endurance-based sports. Conclusion The use of a ketogenic diet by athletes should be considered individually and conducted under professional supervision. Due to potential side effects and the lack of clear evidence for performance enhancement, further well-designed studies are necessary-particularly those considering sex differences and the long-term effects of the diet on the athlete’s body.